Southeast Asian Minorities in the Wartime Japanese Empire. - Kratoska, Paul H. (Taylor and Francis, 2012)
The Japanese invasion and occupation of southeast Asia provided opportunities for the peoples of the region to pursue a wide range of agendas that had little to do with the larger issues which drove the conflict between Japan and the allies. This book explores how the occupation affected various minority groups in the region. It shows, for example, how in some areas of Burma the withdrawal of established authority led to widespread communal violence; how the Indian and Chinese populations of Malaya and Thailand had extensive and often unpleasant interactions with the Japanese; and how in Java.